Contributions of personality to social influence: Contingent associations between social network body size composition and BMI. (March 2019) - Perry, Brea L.; Ciciurkaite, Gabriele
Abstract: Social influence is a key determinant of health behaviors and outcomes. Research in the social network tradition emphasizes social structural mechanisms like network content (i.e., the degree to which particular attitudes, attributes, or behaviors are present in the network) and social proximity (i.e., opportunities for social interaction). In contrast, psychologists are oriented toward the individual, identifying how personality traits like self-monitoring affect susceptibility to peer pressure. Here, we integrate social network and personality approaches, examining social influence on body size using surveys of 379 adults with dependent children. Our findings suggest that the association between social network body size composition and respondent BMI is contingent on both individual susceptibility to influence (i.e., high self-monitoring) and social proximity (i.e., opportunities for co-eating). These results indicate that individuals embedded in social networks bring unique sets of social skills and orientations to interactions, potentially influencing the flow of content across networks. Highlights: Social network and personality approaches to social influence are seldom integrated. Developed a scale to measure self-monitoring of eating behavior in social settings. Found associations between social network body size composition and respondent BMI. Social influence was contingent on individual self-monitoring and social proximity. Personality may affect receptiveness to influence and transmission of network content.